1990
DOI: 10.1152/jappl.1990.68.5.2195
|View full text |Cite
|
Sign up to set email alerts
|

Decline in VO2max with aging in master athletes and sedentary men

Abstract: Fifteen well-trained master endurance athletes [62.0 +/- 2.3 (SE) yr] and 14 sedentary control subjects (61.4 +/- 1.4 yr) were reevaluated after an average follow-up period of approximately 8 yr to obtain information regarding the effects of physical activity on the age-related decline in maximal O2 uptake capacity (VO2max). The master athletes had been training for 10.2 +/- 2.9 yr before initial testing and continued to train during the follow-up period. The sedentary subjects' VO2max declined by an average o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
189
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(204 citation statements)
references
References 0 publications
13
189
2
Order By: Relevance
“…VO 2max , high-intensity aerobic training, and age Although VO 2max typically declines with age, it has been clearly documented that physical activity can counteract this process (Rogers et al 1990;Trappe et al 1996). Indeed, even at baseline, the older subjects in this study were a testament to this concept, being moderately exercise trained, but certainly not among the best runners in their age group, and having an equivalent VO 2max to the young.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…VO 2max , high-intensity aerobic training, and age Although VO 2max typically declines with age, it has been clearly documented that physical activity can counteract this process (Rogers et al 1990;Trappe et al 1996). Indeed, even at baseline, the older subjects in this study were a testament to this concept, being moderately exercise trained, but certainly not among the best runners in their age group, and having an equivalent VO 2max to the young.…”
Section: Discussionmentioning
confidence: 74%
“…Although this decline in aerobic capacity with increasing age is often considered to be inevitable, it seems that this fall can be decelerated, maintained, or even reversed in the elderly by maintaining a high level of physical activity (Faulkner et al 2008;Fujimoto et al 2010;Grimsmo et al 2010;Heath et al 1981;McGuire et al 2001b;Murias et al 2010;Osteras et al 2005;Posner et al 1986;Rogers et al 1990;Trappe et al 2013;Trappe et al 1996). Indeed, marathon running times of approximately 2.5 h or less, documented in males older than 60 years of age, reveal that a VO 2max of ∼70 mL min kg −1 (Helgerud 1994;Tokmakidis et al 1987), a high value exhibited by young endurance athletes at the peak of their careers, is still feasible with increasing age.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] The age-associated decline in maximal oxygen consumption can be attenuated by habitual aerobic exercise, although the mechanism is unclear. [7][8][9][10][11] Although it has been shown that exercise training can augment both cardiac output and the AV oxygen difference in younger subjects, 12,13 these components have not been measured in older subjects before and after exercise intervention.…”
mentioning
confidence: 99%
“…After the peak in young adult age, MAP has been described to decay by about 10 % per 58 decade in the general population after the age of 30 (Åstrand 1973;Dill et al 1967;Maharam et al 1999;Marti and 59 Howland 1990;Marcell et al 2003;Robinson 1938;Rogers et al 1990;Trappe et al 1996), even though we do not 60 know exactly at which age this decay becomes evident.…”
mentioning
confidence: 89%